A reconciliation of empirical and mechanistic models of the air‐sea gas transfer velocity. Issue 1 (24th January 2016) - Goddijn‐Murphy, Lonneke; Woolf, David K.; Callaghan, Adrian H.; Nightingale, Philip D.; Shutler, Jamie D.
Abstract: Models of the air‐sea transfer velocity of gases may be either empirical or mechanistic. Extrapolations of empirical models to an unmeasured gas or to another water temperature can be erroneous if the basis of that extrapolation is flawed. This issue is readily demonstrated for the most well‐known empirical gas transfer velocity models where the influence of bubble‐mediated transfer, which can vary between gases, is not explicitly accounted for. Mechanistic models are hindered by an incomplete knowledge of the mechanisms of air‐sea gas transfer. We describe a hybrid model that incorporates a simple mechanistic view—strictly enforcing a distinction between direct and bubble‐mediated transfer—but also uses parameterizations based on data from eddy flux measurements of dimethyl sulphide (DMS) to calibrate the model together with dual tracer results to evaluate the model. This model underpins simple algorithms that can be easily applied within schemes to calculate local, regional, or global air‐sea fluxes of gases. Key Points: The air‐sea gas transfer model presented is consistent with data on a diverse set of gases Bubble‐mediated air‐sea gas transfer cannot be ignored in strong winds How the void fraction of bubble plumes could affect air‐sea gas transfer velocity is discussed